Effectiveness of Coenzyme Q10 Supplementation for Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis. (16th September 2018) - Zhang, Shi-ying; Yang, Kai-lin; Zeng, Liu-ting; Wu, Xiao-he; Huang, Hui-yong
Abstract : Objective . To evaluate the effectiveness and safety of coenzyme Q10 for patients with type 2 diabetes mellitus (T2DM). Methods . Data from randomized controlled trials were obtained to assess the effects of coenzyme Q10 versus placebo or western medicine on patients with T2DM. The study's registration number is CRD42018088474. The primary outcomes included glycosylated hemoglobin, fasting blood glucose, and fasting insulin. Result . Thirteen trials involving 765 patients were included. Compared with the control group, coenzyme Q10 may decrease the HbA1c (WMD −0.29; 95% CI −0.54, −0.03;P = 0.03 ) and the fasting blood glucose (WMD −11.21; 95% CI −18.99, −3.43;P = 0.005 ). For fasting insulin, there is also not strong evidence that confirms which one is better because there was no statistical difference (WMD −0.48; 95% CI −2.54, 1.57;P = 0.65 ). Conclusion . Based on current evidence, coenzyme Q10 may assist glycemic control, decrease TG, and improve HDL-C in patients with T2DM.